Patterns and Consequences of Alcohol Consumption among Youths in Nsukka Urban. - Nwagu, Evelyn; Odo , Amelia; Dibia, Samuel (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
Heavy or at-risk drinking has remained a problem among young people in many parts of the world. Identifying drinking patterns and their consequences are critical in developing a preventive health education programme for youths. This study was conducted to determine drinking patterns and consequences among youths who were current consumers of alcohol in Nsukka urban. Three research questions and two null hypotheses guided the study. Cross sectional research designed was used for the study while questionnaire was the instrument for data collection. A sample of 500 youths was used for the study. The data were analysed using frequencies and percentages. Null hypotheses were tested at .05 level of significance using the chi square statistics. Greater proportion of male youths than female youths consume alcohol of various brands. The number of male youths who engage in heavy drinking was significantly more than female youths who do so. There was no significant difference at.05 level of significance in the number of youths who drink or engage in at-risk drinking when they were classified by their level of education. It was recommended that appropriate drug education on the health risk of heavy drinking should be given to youths using such means as the electronic media and the internet.